Ending the war between sales and marketing - Turnbull, Andrew (Henry Stewart Talks, 2010)
Sales and marketing defined, Mutual understanding and teamwork, Strategic focus, Target audiences and communication channels, Relationships and cooperation, Shared experiences and added value, Enhanced performances, Barriers to success, Role exploration, Economic, cultural and personal friction, Relationship types, Developing links, The buying funnel